MAKAN ADAT DALAM UPACARA PEMINANGAN LAKI-LAKI SUKU ABUI KEPADA PEREMPUAN SUKU KUI DI KABUPATEN ALOR - Intan Permatasari Lema Madde; Herlofina Manikafola, Heronike Mangmani,Neziah Hinagay, Inggrit E.Bayang, Henderina Womakal, Inang N (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The purpose of this study was to study the customary meal in the marriage ceremony of Abui tribe men to Kui tribe women in Alor district. This research uses qualitative methods with an ethnographic approach. Data analysis techniques were carried out by means of data reduction and conclusion drawing. the research was conducted at Matalafang Tourism, west lembur village, north central alor sub-district, alor district. The informant in this research is the customary head of Matalafang. The results of this study are eating customs in the Abui tribe men's engagement to Kui tribe women. One of the customs that is still maintained until now is the traditional meal in the male engagement ceremony for women. The proposal from Abui men to Kui women is one part of the marriage procession of the Abui and Kui communities. In conducting the proposal ceremony, both parties are represented by their respective spokespersons. In general, the customary food of the Abui tribe and the Kui tribe in the engagement ceremony has similarities, where families bring rice and also animals.